PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR SENI RUPA SISWA KELAS X DI SMA NEGERI 3 PARIAMAN - SILVIA ANGGRAINI, Dra. Zubaidah, M.Pd., Drs. Erwin A, M.Sn. (Serupa The Journal of Art Education, 2016)
The following research is purposed to described the influence of applying cooperative model for type of Student Teams Achievement Division (STAD) towards learning’s result of Art class for tenth grade at senior high school number 3 in Pariaman. This research is using quantitative method with an experiment model. the instrument is using learning’s result test. Afterwards, the data is processed by using SPSS program version 16.00. Based on hypothesis testing by using SPSS program version 16.00, obtained that t (count) is 5.314 and t (tabel) is 2.034 with significance of level 5% (α = 0,05). It shows that there is significance difference between two classes. Therefore, it is concluded that applying cooperative model for type of Student Teams Achievement Division (STAD) has a positive influence toward learning’s result of Art class for tenth grade high school number 3 in Pariaman.Kata Kunci: Model pembelajaran kooperatif tipe STAD dan hasil belajar